The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009 3rd International Conference on Bioinformatics and Biomedical Engineering 2009
DOI: 10.1109/icbbe.2009.5162223
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Study the Contribution of Stretch Reflexes During Dynamic Voluntary Tasks

Abstract: A method was tested to extract reliable estimates o f stretch reflex gain during a simple upper limb task involving dynamic muscle contractions. The gain estimates obtained from a 10hz sinusoidal stretch perturbation were comparable in dynamic tasks and constant contractions of similar average magnitude. It was concluded that the method may permit studies of functionally related changes in reflex gain during upper limb tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…In the study of Xia et al ( 2005 ), it was observed that stretch-reflex amplitudes were roughly modulated in a sinusoidal fashion such that increased reflex amplitudes were associated with higher background FDS EMG levels. A similar conclusion was reached by Stanislaus and Burne ( 2009 ), who reported a consistent relationship between stretch-reflex gain and overall contraction level regardless of force dynamics. If a similar sinusoidal modulation of reflex gain were responsible for tremor modulation in our study, we should have observed a sinusoidal modulation of tremor amplitude, which was not the case.…”
Section: Discussionsupporting
confidence: 85%
“…In the study of Xia et al ( 2005 ), it was observed that stretch-reflex amplitudes were roughly modulated in a sinusoidal fashion such that increased reflex amplitudes were associated with higher background FDS EMG levels. A similar conclusion was reached by Stanislaus and Burne ( 2009 ), who reported a consistent relationship between stretch-reflex gain and overall contraction level regardless of force dynamics. If a similar sinusoidal modulation of reflex gain were responsible for tremor modulation in our study, we should have observed a sinusoidal modulation of tremor amplitude, which was not the case.…”
Section: Discussionsupporting
confidence: 85%